2016
DOI: 10.1016/j.jcin.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Varying Revascularization Strategies in Patients With ST-Segment Elevation Myocardial Infarction and Multivessel Coronary Artery Disease

Abstract: The present systematic review and meta-analysis supports the hypothesis that in patients with MV-CAD presenting with STEMI undergoing primary PCI, a staged multivessel revascularization strategy may improve early and late survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 46 publications
2
28
3
1
Order By: Relevance
“…This showed that immediate complete revascularization might be more superior compared to staged revascularization. This finding seems to be opposite of what was found in other metaanalyses (40,44) and the few observational studies (45,46).…”
Section: Timing Of Revascularizationcontrasting
confidence: 90%
See 2 more Smart Citations
“…This showed that immediate complete revascularization might be more superior compared to staged revascularization. This finding seems to be opposite of what was found in other metaanalyses (40,44) and the few observational studies (45,46).…”
Section: Timing Of Revascularizationcontrasting
confidence: 90%
“…This study showed that MV-PCI during index procedure was associated with an increased all-cause mortality [hazard ratio (HR) 4.1, 95% CI: 1.93-8.86, P<0.0001] and cardiovascular mortality (HR 3.41, 95% CI: 1.35-7.27, P=0.005) compared to the staged MV-PCI (45). Similarly, a meta-analysis by Tarantini et al (40) revealed that staged revascularization was associated with short-and long-term survival compared with both immediate complete revascularization and culprit-only revascularization. In separate meta-analysis by Li et al (44) which compared staged revascularization and immediate complete revascularization head-to-head, the former seemed to be a better strategy.…”
Section: Timing Of Revascularizationmentioning
confidence: 95%
See 1 more Smart Citation
“…Even though we had published the data concerning 1‐year clinical outcomes between the same generation stents in patients with STEMI with MVD, the comparative studies that focused on the long‐term clinical outcomes of different generations of stents in STEMI patients with MVD after C‐PCI or M‐PCI are rare. M‐PCI carries the risk of procedural complications during PCI of nonculprit lesions, such as abrupt vessel closure and stent thrombosis, may be increased in the prothrombotic and proinflammatory state that characterizes STEMI compared with C‐PCI . The main differences between C‐PCI and M‐PCI are total procedure time, time interval between index PCI and staged PCI, and the possibility for the exposure to those unfavorable situations.…”
Section: Discussionmentioning
confidence: 99%
“…While the American College of Cardiology (ACC)/American Heart Association (AHA) upgraded the recommendation for non‐IRA PCI at the time of index procedure or as staged procedure from III to IIb, giving an equal level of recommendation to both index procedure and staged revascularization, the European Society of Cardiology (ESC) gives a IIa recommendation for staged revascularization of non‐IRA and IIb for index procedure revascularization . A recent metanalysis of observational and randomized controlled studies by Tarantini et al and a British Columbia Cardiac Registry study have both demonstrated lower mortality and repeat revascularization with staged multivessel intervention (MVI‐S) compared to index procedure multivessel intervention (MVI‐I). The goal of the current study was to compare any staged, but complete revascularization with complete revascularization at the time of the index STEMI PCI procedure in patients with multivessel CAD presenting with STEMI.…”
Section: Introductionmentioning
confidence: 99%